A Preliminary Exploration of the Stability of Music- and Photo-Evoked Autobiographical Memories in People with Alzheimer's and Behavioral Variant Frontotemporal Dementia. (17th September 2020) - Baird, Amee; Gelding, Rebecca; Brancatisano, Olivia; Thompson, William Forde
Music evoked autobiographical memories (MEAMs) occur in people with Alzheimer's dementia (AD), but there is limited study of such memories in people with other dementia types such as behavioral variant frontotemporal dementia (Bv-FTD). Furthermore, there has been no study of the integrity of such memories over time, and scarce comparison with other memory cues such as photos. Our aim was to address this current gap in our knowledge and to characterize MEAMs and photo-evoked autobiographical memories (PEAMs) in healthy elderly people and people with AD and Bv-FTD on two occasions, 6 months apart. Twenty-two participants (7 with AD, 6 with Bv-FTD, and 9 healthy elderly people) reported memories following exposure to two famous songs and two famous event photographs from each decade from 1930–2010 on two occasions. All people with AD and all healthy elderly controls reported at least one MEAM or PEAM at both times. In contrast, two people with Bv-FTD reported no memories at either time. The percentage of memories over time for songs and photos remained stable for the Healthy Elderly and AD groups, whilst the percentage of memories to songs increased over time for people with Bv-FTD. Songs elicited more positive memories than photos. The specific music and photo stimuli that triggered memories, and the topic of the memories that were evoked, remained stable over a 6-month period across all groups. Our results suggest that music and photos are efficient memory cues in people with AD and Bv-FTD. Future large-scale studies of people with different dementia types over a longer time period will provide insights into the integrity of music- and photo-evoked autobiographical memories as dementia progresses.